SOSIALISASI TENTANG NIKAH SIRI: PERSEPEKTIF HUKUM ISLAM DAN HUKUM POSITIF DI KELAS XII MA DAARUL QUR’AN KOSAMBI - Dewi, Puspita Komala; Fadilah, Raghil; Mita, Reginas Weri Laras; Sakinah; Bariah, Oyoh (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aimed to provide adolescents with a deeper understanding of the legal and social consequences of the practice of unregistered marriage through socialization to grade XII students of MA Daarul Qur'an Kosambi. The socialization was in the form of an explanation of the definition of unregistered marriage, the differences with official marriage, and the negative impacts that arise, such as uncertainty of legal status and problems in family relationships. In addition, the socialization also included education about divorce, by highlighting the correct procedures and the importance of communication in resolving household problems. The method of implementing the activity was in the form of lectures, interactive discussions, and questions and answers, so that it is hoped that students can become more critical and responsive to issues surrounding marriage and divorce, while encouraging the application of positive values ​​in family life. The stages of implementing the community service activity started from preparation, implementation, and evaluation of the activity. The results of this activity make adolescents understand the importance of a marriage that is valid according to religion and law, and are able to make wise decisions in forming a family in the future.